Monthly Income and Quality of Work Life of Public and Private Sector Employees of Kerala - Ambily A.S (Journal of Management Research and Analysis, 2015)
Quality of work life encompasses various aspects relating to work environment, employee motivation, technology facilities, quality and humanism of managerial care and supervision, management – union relations and so on. The level of economic development considerably determines people’s quality of life. Organisations’ role is crucial in attracting competent, talented persons, and to retain them. It constantly adds significant value to the organisation. For retaining the employees’ of the organisation, monthly income has a significant role. Employees’ compensation, gives a sense of recognition and also determines social status. Employees’ compensation is a vital issue that needs an immediate solution. Present study focuses on monthly income and Quality of work life of public and private sector employees of Kerala.